Somatic Transformations in the Context of Antropotechnogynesis at the Modern Stage - І. Р. Pecheranskyi (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose. The main purpose of the article is the analysis of the phenomenon and manifestations of the somatic transformations in the context of anthropo-technological evolution at the beginning of the XXI century. Theoretical basis. The author determines the understanding of the concept "somatic transformations" in the frames of anthropotechnogynesis is possible only on the base of integrative approach and combination of post-non-classical scientific paradigm methodology, theory of the technological development, ideas of trans-humanism, informative society concepts, and net technologies influence on the identity of the human being with robots in the sphere of bioethics and nanoethics, the ethics of new technologies and legal documents which are regulating the processes of technotransformation of the human being. Originality. The author has proved on the example of analysis of the somatic transformations own psychosomatics as he solves some important global in the context of anthropotechnogynesis that a person with help of technological enlargement of and branch problems, so he is trapped of alienation in the very crucial stage, loses the identity and crashes the corporeality in his self. Conclusions. As evidenced by the given analysis, at the modern stage the anthropotechnogynesis is followed by the large-scale quantitative and qualitative somatic transformations based on NBIC-convergence, as a result, a new anthropological subspecies – Homo technologicus appears. All these transformations are a regular stage of evolution, which confirms the thesis of the essential and functional connection of technology with the human body, which are in a relationship of "mutual provocation". In the base of the paradigmatic ontological and anthropological shift which has been on the modern stage, lies the idea of continuity of anthropotechnological co-evolution of the human body and its environment which projects itself in psychosomatic human structure, making a transformation program for better adaptation in technonanobeing. The convergence of human life and techno-existence is a platform for somatic transformations. They are divided into two main groups: intra-structural, substantial, related to techno-modification of the human body directly through biotechnology and genetic engineering, cyborgization, xenotransplantation, Hi-Hume connection with Hi-Tech and others, and external-contextual, when under the influence of pancommunication and hybridization the environment is increasingly mentalized and somatized, and modern technologies are gradually transformed into the social body of man.